2022
DOI: 10.1038/s41419-022-05379-3
|View full text |Cite
|
Sign up to set email alerts
|

RHBDL2 promotes the proliferation, migration, and invasion of pancreatic cancer by stabilizing the N1ICD via the OTUD7B and activating the Notch signaling pathway

Abstract: Pancreatic cancer (PC) is one of the most malignant types of cancer, and is characterized by early metastasis, limited response to chemotherapeutics, and poor prognosis. Therefore, there is an urgent need to explore new therapeutic strategies for PC treatment. Human rhomboid-like 2 (RHBDL2) is differentially expressed in cervical and breast cancer. However, the correlation between RHBDL2 and PC remains unclear. We found that RHBDL2 is highly expressed in human PC cells and tissues and is significantly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, these genes have also been reported to be associated with the occurrence and development of other types of tumors. For example, OTUD7B has been reported to play a critical role in activating mTORC2/AKT signaling and promoting lung cancer, [ 27 ] and its abnormal expression is also associated with the progression of breast cancer, [ 28 ] pancreatic cancer, [ 29 ] and liver cancer. [ 30 ] High expression of AP1S3 is closely related to the proliferation, invasion, and migration of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, these genes have also been reported to be associated with the occurrence and development of other types of tumors. For example, OTUD7B has been reported to play a critical role in activating mTORC2/AKT signaling and promoting lung cancer, [ 27 ] and its abnormal expression is also associated with the progression of breast cancer, [ 28 ] pancreatic cancer, [ 29 ] and liver cancer. [ 30 ] High expression of AP1S3 is closely related to the proliferation, invasion, and migration of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of OTUD7B has been observed in several types of cancer, such as lung, breast, liver, and pancreatic cancers. In these cancers, the upregulation of OTUD7B promotes the stabilization and activation of TRAF3, estrogen receptor α, and N1ICD, leading to uncontrolled cell growth and tumor formation [ 31 , 32 , 33 , 34 , 35 , 36 ]. Conversely, downregulation of OTUD7B has been associated with impaired DNA damage response and increased genomic instability [ 29 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a deubiquitinating enzyme (DUB), it regulates many important cellular signaling pathways, such as those related to inflammation, scar formation, and T cell activation 16,17 . Accumulating data suggested that OTUD7B expression directly affected the survival rate of various solid tumors, such as lung cancer, liver cancer, breast cancer, or pancreatic cancer, and played a potential role in cancer cell proliferation 18–21 . It has recently been shown that OTUD7B attenuates the ubiquitination level of N1ICD (Notch1 intracellular domain) by binding to RHBDL2 (rhomboid‐like 2 protein), thereby activating Notch signaling 18 …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Accumulating data suggested that OTUD7B expression directly affected the survival rate of various solid tumors, such as lung cancer, liver cancer, breast cancer, or pancreatic cancer, and played a potential role in cancer cell proliferation. [18][19][20][21] It has recently been shown that OTUD7B attenuates the ubiquitination level of N1ICD (Notch1 intracellular domain) by binding to RHBDL2 (rhomboid-like 2 protein), thereby activating Notch signaling. 18 Based on the above findings, we sought to elucidate a novel mechanism by which OTUD7B inhibits lung cancer fine progression under hyperthermia conditions, and provide new insights into the occurrence and development of lung cancer and anti-tumor therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation